RANCANG BANGUN APLIKASI FRONT END MANAJEMEN SURAT MASUK dan KELUAR SEKRETARIAT DPRD PROVINSI BALI - wayabia, nyoman bramanta; Mahendra, Ida Bagus Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 7 No 3 (2019): JELIKU Volume 7 No 3, Februari 2019, 2019)
The official departure activities of PNS (Civil Employee) and Members of the DPRD of the Province of Bali are one of the programs of activities that are often carried out. Filing in official travel activities that while still running is considered vulnerable to problems in filing and searching because it is still manual and archiving is still using paper so that it is easily lost. In order to help the administrative staff who take care of official travel, therefore this research was made. This study uses the waterfall method in the development of the system which includes stages of analysis and definition, system design, implementation and unit testing, system integration and testing, operation and maintenance. While the data collection is done by observation and manual data collection. System modeling used is the UML (Unified Modeling Language) modeling language and is web-based with the PHP (Hypertext Preprocessor) programming language and mysql database. The results of this study can facilitate all parts related to official travel activities both in storing data on notes and assignment letters, warrants, reports on control of official travel orders control.